Plainness of Speech, Behaviour and Apparel in Eighteenth-Century English Quakerism - Hall, David J. (Studies in church history, 1985)
The aim of this communication is to illustrate and examine the official attitude of the Quakers to their testimony on plainness in the eighteenth century, with a few examples, limited by available space, of the opinions of individuals. It is also limited to England since official attitudes in America and Ireland were somewhat different; it attempts no comparison with other contemporary English traditions; it cannot do more than touch on such gaps as may have existed between individual practice and official attitude; nor can it make use of the ample surviving local records. To understand what lay behind the testimony on plainness it is necessary to go back briefly to the rise of Quakerism in the mid-seventeenth century.